2017
DOI: 10.15376/biores.12.4.8490-8504
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of biocompatible hydrogel from lignin-carbohydrate complex (LCC) as cell carriers

Abstract: Two poplar lignin-carbohydrate complexes (LCCs), LCC-48 and LCC-72, were isolated at different milling times, 48 h and 72 h, respectively. A new hydrogel carrier was prepared from these LCCs in the presence of polyethylene glycol diglycidyl ether as the crosslinker for cell (human hepatocyte (L-02)) culture. The effects of the structure of LCC on the carrier were investigated. The FT-IR spectra indicate that the two LCC samples were composed of lignin and polysaccharide, and showed a typical LCC structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…It should be pointed out that the signals for ester bonds in LCCs is overlapped with signals of γ-acylated β-O-4 aryl ethers; the calculated esters in LCCs is inevitably overestimated, which has also been reported by Yuan et al 15 and You et al 31 Overall, the different amounts of LCCs linkages will result in the amounts and types of the associated carbohydrates in LCCs preparations, which can further affect their biobased application. 6,21 Antioxidant Activities of LCCs-Bjorkman on Scavenging DPPH and Superoxide Anion Radical. Our above results revealed that the LCCs-Bjorkman preparations investigated in this work mostly contain fractions of lignin and carbohydrate (xylan).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be pointed out that the signals for ester bonds in LCCs is overlapped with signals of γ-acylated β-O-4 aryl ethers; the calculated esters in LCCs is inevitably overestimated, which has also been reported by Yuan et al 15 and You et al 31 Overall, the different amounts of LCCs linkages will result in the amounts and types of the associated carbohydrates in LCCs preparations, which can further affect their biobased application. 6,21 Antioxidant Activities of LCCs-Bjorkman on Scavenging DPPH and Superoxide Anion Radical. Our above results revealed that the LCCs-Bjorkman preparations investigated in this work mostly contain fractions of lignin and carbohydrate (xylan).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…7,9 The different proportions of carbohydrate and lignin in these LCC preparations result in different physical and chemical properties, including water solubility, molecular weight, and biological activity. 6,13 It is generally accepted that the Bjorkman LCCs is the classical LCCs preparation, serving as a substrate for their chemical and functional properties, valuable linkages analysis, and application. 12 To obtain compositional and structural information on LCCs preparations, various chemistry and spectroscopic methods can be applied.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin-derived hydrogels have also been mentioned as possible 'vehicles' for human hepatocyte cell cultures. Indeed, it was shown that the porous nature of the hydrogel facilitated the adsorption of the cells to the pores which resulted in increased metabolic activity and cell proliferation (Zhao et al, 2017). Additional studies have also shown that for lignin-based hydrogel systems characterized by the immobilization of lipase, the presence of lignin enhances the activity and stability of the enzymes compared to systems without this biopolymer Park, Kim, Won, et al, 2015).…”
Section: Development Of Hydrogelsmentioning
confidence: 99%
“…The high mechanical strength and resistance to biodegradation of woody cell walls is thought to stem from the structure of lignin-carbohydrate complexes (LCCs) in wood (Toikka et al 1998). LCCs from natural plant have important applications in materials and alternative medicine (Zhao et al 2017a(Zhao et al , 2017bSakagami et al 2010). However, the isolation efficiency of LCCs from natural plant is not high, which limits its application.…”
Section: Introductionmentioning
confidence: 99%